2015
DOI: 10.1002/pola.27746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of new phosphonic acid‐functionalized acrylamides with potential biomedical applications

Abstract: Phosphorus‐containing acidic monomers are able to interact with the inorganic phase of mineralized tissues such as enamel, dentin, and bone. From this perspective, three phosphonic acid‐containing acrylamide monomers with different lengths of alkyl chains were synthesized to be used for both self‐etching dental adhesives and mineralized hydrogel scaffolds. Monomers were synthesized by the reaction of α‐aminophosphonates (diethyl aminomethylphosphonate, diethyl 2‐aminobutan‐2‐ylphosphonate, and diethyl 2‐aminoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Phosphorous-containing polymers have been implemented to improve and accelerate the formation of native tissue both by mimicking the native role of phosphorous groups in the body and by attachment of other bioactive molecules . The hydrogels containing phosphate and phosphonate groups mineralize faster and more completely than analogues lacking the phosphorus-containing groups and also feature better cell adhesion and growth. In this context, Gemeinhart et al developed a copolymer hydrogel of vinyl phosphonic acid (VPA) and acrylamide and found that at 30% VPA concentration, osteoblast-like cells exhibit better proliferation, adhesion, differentiation, and ability to mineralize the polymer surface than at other concentrations of VPA; other work observed that ethylene glycol methacrylate phosphate-containing poly­(ethylene glycol) (PEG) diacrylate hydrogels promote human mesenchymal stem cells adhesion and spreading; and hydrogels based on a phosphoester–PEG polymer promoted the gene expression of bone-specific markers including type I collagen and osteonectin without the addition of growth factors or other biological agents, compared with pure PEG-based gels …”
Section: Introductionmentioning
confidence: 99%
“…Phosphorous-containing polymers have been implemented to improve and accelerate the formation of native tissue both by mimicking the native role of phosphorous groups in the body and by attachment of other bioactive molecules . The hydrogels containing phosphate and phosphonate groups mineralize faster and more completely than analogues lacking the phosphorus-containing groups and also feature better cell adhesion and growth. In this context, Gemeinhart et al developed a copolymer hydrogel of vinyl phosphonic acid (VPA) and acrylamide and found that at 30% VPA concentration, osteoblast-like cells exhibit better proliferation, adhesion, differentiation, and ability to mineralize the polymer surface than at other concentrations of VPA; other work observed that ethylene glycol methacrylate phosphate-containing poly­(ethylene glycol) (PEG) diacrylate hydrogels promote human mesenchymal stem cells adhesion and spreading; and hydrogels based on a phosphoester–PEG polymer promoted the gene expression of bone-specific markers including type I collagen and osteonectin without the addition of growth factors or other biological agents, compared with pure PEG-based gels …”
Section: Introductionmentioning
confidence: 99%